The Effect of Claustrophobic Tendencies on Digital Spatial Preferences - Chung, Sorim (Frontiers in Psychology, 2022)
In digital environments, the demand for larger devices (e.g., larger smartphones) has been growing continuously, indicating users’ spatial needs in digital interfaces. This study explores the need for space in digital interfaces in relation to claustrophobic tendencies. The findings from two studies consistently report that (1) stronger claustrophobic tendencies toward physical spatial constraints are positively associated with a stronger need for digital space. The results also demonstrate that (2) people with elevated claustrophobic tendencies and a stronger need for digital space perceive stronger spatial constraints on digital interfaces, and (3) claustrophobic tendencies and the need for digital space have stronger effects on spatial constraints with a more complex grid design. Interestingly, the findings suggest that (4) claustrophobic tendencies are more closely associated with spatial needs from attentive tasks (e.g., reading a long document), than device-related spatial needs (e.g., large screen preferences), implying that such claustrophobic tendencies are more likely to influence cognitive tasks on digital devices. Overall, the findings indicate that claustrophobic tendencies may be utilized beyond medical purposes and may assist researchers and business practitioners understand users’ spatial needs in fast-changing digital environments.